علاقة بعض الصفات الشكلية للأنف مع نموذج النمو الوجهي حسب Jarabak - حسن, عبد الكريم; محرز, علاء (Latakia University Journal -Medical Sciences Series, 2016)
تهدف هذه الدراسة إلى تقييم وتحليل بعض الصفات الشكلية للأنف ودراسة علاقتها مع نماذج النمو الوجهي حسب Jarabak واختلافاتها بين الجنسين . حيث تمت دراسة الصور الشعاعية السيفالومترية الجانبية للرأس لعينة مؤلفة من 31 أنثى و55 ذكر تراوحت أعمارهم بين 18-25 سنة وباستخدام تحليل التباين Kruskall-Wallis one-way ANOVA و اختبار Mann-Whitney U-tests الإحصائية.• أظهرت النتائج وجود علاقة هامة إحصائيا بين كل من زاوية قاعدة القحف مع العظم الأنفي ( Nasal bone/SN)، والمستوى الأنفي مع قاعدة القحف( NSL/NL)، ونمط الوجه عند جميع المشاركين. ولوحظ عند الذكور وجود علاقة هامة إحصائيا بين كل من طول الغضروف الأنفي(Cart-nose)، والطول الكل للأنف Tot-nose))، والزاوية بين العظم الأنفي مع قاعدة القحف( ( Nasal bone/SN، Clumellar-labia) angel )ونمط الوجه.بينما أظهرت النتائج عند الإناث وجود علاقة هامة إحصائياً بين كل من زاوية العظم الأنفي مع قاعدة القحف (Nasal bone/SN) ، والمستوى الأنفي مع قاعدة القحف (( NSL/NL، ونمط الوجه .The aim of this study was to assess and analysis the morphology of the nose and examine their relationships with the facial growth types according to Jarabak and their differences between the sexes This study is performed with using radiographic cephalometric for 31 female and 55 male aged between 18-25 years and by using analysis of variance Kruskall-Wallis one-way ANOVA and Mann-Whitney U-tests of statistical test. The results showed a statistically significant relationship between each of the angle Cranial base with the nasal bone (Nasal bone / SN), and level of the nose with cranial base (NSL / NL), and the facial pattern for all the simple. It was noted the existence of a significant statistical relationship between the length of the nasal cartilage (Cart-nose), and the total length of the nose , and the angle between the nasal bone with cranial base and facial pattern .And the results showed at females the presence statistically significant relationship between each of the( Nasal bone / SN), and (NSL / NL), and facial pattern.